BILINGUALISM AND THE CULTURAL IMPERIALISM OF LANGUAGE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Bilingualism, the ability to speak two or more languages fluently, is a common phenomenon worldwide, influenced by historical, social, and cultural factors. However, when examined through the lens of cultural imperialism, bilingualism becomes a complex topic. The dominance of one language over others can lead to the erosion of minority languages, creating a cultural hierarchy where one language and its associated culture are privileged over others. This paper explores the impact of bilingualism on cultural imperialism, arguing that while bilingualism can be an empowering tool for communication, it can also perpetuate linguistic dominance and cultural inequality.